Studi Analisis Pelaksanaan Model Pembelajaran Discovery Learning oleh Guru PPKn di SMA Negeri 6 Balikpapan - Widya Apriliyana Wijiani; A. Hardoko; M. Jamil (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study is to determine how the implementation of the discovery learning model by PPKn Teachers of SMA Negeri 6 Balikpapan in the Discovery Learning Syntax by PPKn Teachers of SMA Negeri 6 Balikpapan. This type of research aims to analyze the implementation of the discovery learning model by PPKn teachers at SMA Negeri 6 Balikpapan. The research was conducted in March 2024. The research subjects were 3 Student Respondents with high, medium and low criteria and 1 PPKn Teacher Informant. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of this study show the implementation of the Discovery Learning learning model by PPKn teachers in the Pancasila and Citizenship Education (PPKn) subject at SMA Negeri 6 Balikpapan. The results of the study during the observation of PPKn teachers at SMA Negeri 6 Balikpapan applied six Discovery Learning syntaxes, namely: (1) Stimulation, (2) Problem Statement, (3) Data Collection, (4) Data Processing, (5) Verification, and (6) Generalization. The implementation of the syntax has generally gone well, as indicated by several indicators such as active involvement of students in the learning process, increased student analytical skills and a deeper understanding of the concept of discovery learning and student enthusiasm in participating in learning. The Discovery Learning learning model can be used as an alternative problem solving in PPKn learning, because this model prioritizes the discovery process to obtain stages to train students' abilities in both cognitive, affective and psychomotor domains. Teachers in implementing discovery learning according to its syntax so that the learning process in the classroom runs well where students actively follow the lesson, so that students' mastery of the subject matter shows an increase. This is indicated by the test results given by the teacher. With the discovery learning model, PPKn learning in the classroom is more enjoyable.